(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic has completely changed the economic, social and educational landscapes around the world. Formal education has been marked by the transition from face-to-face to remote education, but all this transition occurred suddenly and unexpectedly and, in many cases, teachers were not prepared and had not enough time to adapt to the new reality. Among the different areas of teaching, the disciplines of the exact sciences field have suffered a serious blow during this transitional period (remote * face-to-face), because, generally speaking, these are the subjects which rely mostly on practical / expository classes, where excessive use of the blackboard is made to demonstrate equations and also for problem solving. Faced with these difficulties, concerns have arisen about the quality of teaching as well as their psychological well-being, as teachers often find themselves overwhelmed, trying to adapt to such changes. Aiming to better understand the landscape of remote education during the pandemic, a survey was conducted with physics teachers from high school (MS), Youth and Adult Education (EJA) and Higher Education (ES), who teach the discipline of Physics in educational institutions as well as public and private companies throughout Brazil, in order to understand, from the teacher’s perspective, how the transition to remote classes has developed, how the experience has been like and also how the teacher sees post-pandemic Physics Teaching.